Gaming motivation and well-being among Norwegian adult gamers: the role of gender and disability - Hygen, Beate W.; Wendelborg, Christian; Solstad, Bård Erlend; Stenseng, Frode; Øverland, Mari Bore; Skalicka, Vera (Frontiers in Medical Technology, 2024)
Introduction: Digital gaming is a popular and often social activity, also among adults. However, we need more knowledge of the social dynamics of gaming and its potential benefits for one's wellbeing. The current study aimed to examine gaming motivation, time spent gaming, and gaming performed together with friends, family, or romantic partner and how these aspects relate to expanded social network and well-being among men and women with and without disability.Methods: Regular players of the popular game Fortnite Battle Royale (FBR; N=278, 48.5% women, Mage = 32.38) completed an online questionnaire assessing their motivations for playing FBR (social motivation, achievement motivation, novelty motivation), time spent gaming, whom they usually play with, their psychological well-being, and FBR's impact on their life and social network. Differentiated statistical analyses on gender and disability were performed.The results showed that time spent gaming and social motivation to play were associated with larger social networks for all participants (strongest for women). More time spent gaming FBR was also associated with a positive impact on life for those with a disability. Social motivation to play was positively associated with a positive impact on life for men and those without a disability and increased well-being for women. Novelty motivation, which concerns experiencing new features in the game, was associated with a positive impact on life for women and with a decrease in well-being for those with a disability. This study demonstrated that gaming can be an essential social arena associated with positive outcomes for men, women and disabled people, who-when socially motivated-may expand their social networks through gaming.